A sociocultural study on solar photovoltaic energy system in India: Stratification and policy implication. (10th April 2019) - Padmanathan, K.; Govindarajan, Uma; Ramachandaramurthy, Vigna K.; Rajagopalan, Arul; Pachaivannan, Nammalvar; Sowmmiya, U.; Padmanaban, Sanjeevikumar; Holm-Nielsen, Jens Bo; Xavier, S.; Periasamy, Senthil Kumar
Abstract: Cleaner production is a simple defensive mechanism to protect the environment from pollution and depletion of resources. It is also envisioned to minimise the waste and capitalise on natural resources with effective utilization. Solar energy is a natural resource which can be converted into electricity using photovoltaic (PV) system. This article sheds insights on the implementation of solar PV system with interdisciplinary views and analyse motives and barriers for PV adoption by different citizen groups in India. A survey was conducted to understand the people's perception on solar PV energy system and to determine the level of acceptability among the citizens. The survey information was synthesised and consolidated from various perspectives and the result consigns the research findings into technical, human and socio-economic components. The findings were synthesised through cross-cultural, comparative and mixed-method research outcomes by means of Structural Equation Modelling (SEM), Dendrogram diagram and biplot interpretation. Statistical tools such as 'IBM-SPSS Amos' and 'R' language programming were also used to interpret the results. This article concludes by specifying the barriers that limit the retrofitting interventions, suggests possible measures and policies to overcome such barriers and promote solar energy in India. Graphical abstract: Image 10812 Highlights: Rethinking: Sustainability and progress of solar energy sector in India. Key influence on energy policy and solar PV energy system. Energy policy-strategy set leveraging statistical methods for participatory planning. Policy implication for Solar PV energy system on the basis of pan-India survey. Identified major challenges associated with solar energy policy implementation.